Analysis Of Determinants Of Maternal Mortality In Rural Areas: A Retrospective Study Based On Routine Health Office Data - Retni, Retni (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The Maternal Mortality Rate in Indonesia is still relatively high, namely 305/100,000 KH. The number of maternal deaths in West Java Province in 2020 was 745 cases. The causes of maternal death are still dominated by bleeding 28% and hypertension 29%. Indramayu Regency reported 61 cases in 2018, 40 cases in 2019 and 38 cases in 2020. The purpose of this study was to analyze the close determinants, intermediate determinants and distant determinants of maternal death in Indramayu Regency in 2020. This type of research is observational analytic with a case control study design. The sample was 38 case groups and the control group was 76 mothers giving birth. Data analysis includes univariate analysis, bivariate analysis (Chi-Square) and multivariate analysis using logistic regression. The results showed a relationship between close determinants pregnancy complications (p value 0.000), childbirth complications (p value 0.000) postpartum complications (p value 0.000) with maternal mortality. There is a relationship between the quality of service (p value 0.000) with maternal mortality. There is a relationship between distant determinants of education (p value 0.017) with maternal mortality. There is no relationship between anemia status (p value 0.399), antenatal examination (p value 0.276) with maternal mortality, There is no relationship between distant determinants of work (p value 0.331), economic status (p value 0.789) with maternal mortality. The most dominant factor related to maternal mortality is pregnancy complications with (p value 0.000).